The Effects of Jigsaw, Student Teams Achievement Divisions (Stad), and Think-Pair-Share (Tps) Techniques in Writing Narrative Text - Sari, Ika Purnama; Susiani, Susiani (Journal of Educational Sciences, 2021)
Writing ability at The Second Semester Students in one of Private High School in Pemtangsiantar indicated low enough. The aim of this research is to find out the effect of three cooperative learning techniques, namely, Jigsaw, Students Teams – Achievement Division (STAD) and Think-Pair-Share (TPS). The research design used in this study was quantitative approach with an experimental. The samples were Second Semester Students of STIKOM Tunas Bangsa Pematangsiantar. The data of this research were gained from the score Narrative Text Test that analyzed by using One Way ANNOVA. The research finding showed that (1) Jigsaw Sig. (2-tailed) value is 0.00 < 0.05. STAD Sig. (2-tailed) value is 0.00 < 0.05. TPS Sig. (2-tailed) value is 0.00 < 0.05, it means Jigsaw, STAD and TPS can affect the students ability in writing. (2) The increasing percentage of Jigsaw Teaching Technique to 75%, Students Teams – Achievement Division (STAD) to 68% and Think-Pair-Share (TPS) to 57%. (3) The result of data Analysis by One Way Annova indicate that Significant values is 0.043 which is < 0.05, and Fvalue is 3.305 > T Table 3.16, it means there is one Teaching Technique more significant there the other technique. Here Jigsaw Teaching Technique more Significant than STAD or TPS. In Jigsaw Teaching Technique, The mean difference is significant at the 0.05 level.